Artificial insemination of bottlenose dolphins (Tursiops truncatus): A trial with simple instruments based on criteria for estrous behaviors linked to changes in estradiol levels and follicle development - Shusaku SAWA; Narumi KAWAHIRO; Minami W. OKUYAMA (The Journal of Reproduction and Development)
Herein, we report a case of pregnancy of a female bottlenose dolphin (Tursiops truncatus) that was subjected to artificial insemination (AI) in water based on its estrous behavior using simple instruments. AI was performed on this female dolphin once or twice daily for 4 days at the detection of estrous behavior, such as floating horizontally and showing reduced responsiveness, likely indicating the appropriate timing for AI. The female was placed in supine a position in the water to position the genital slit above the water surface. A Nélaton catheter (Fr. 10, 40 cm length), with its tip modified, was inserted approximately 20 cm into the vagina through the genital slit, and 1–2 ml of fresh semen was injected. The AI procedure was performed within 1 min by two technicians. Thus, this AI method may be a new choice for artificial reproduction, as pregnancy success can be achieved with relatively less cost, less difficulty, and less invasive treatments of cetaceans.